2023
DOI: 10.1200/po.22.00546
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Next-Generation Sequencing Versus Single-Gene Testing for the Molecular Diagnosis of Patients With Metastatic Non–Small-Cell Lung Cancer From the Perspective of Spanish Reference Centers

Abstract: PURPOSE The aim of this study was to assess the cost-effectiveness of using next-generation sequencing (NGS) versus single-gene testing (SgT) for the detection of genetic molecular subtypes and oncogenic markers in patients with advanced non–small-cell lung cancer (NSCLC) in the setting of Spanish reference centers. METHODS A joint model combining decision tree with partitioned survival models was developed. A two-round consensus panel was performed to describe clinical practice of Spanish reference centers, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Both the Focus Group and the reviewed literature emphasize this aspect, including a previous study showing that the determination of some of the biomarkers is funded by different pharmaceutical companies in more than 50% of the hospitals [ 5 ]. Moreover, it has recently been estimated that the analysis of molecular diagnosis by NGS versus sequential single testing in metastatic non-small cell lung cancer patients from a Spanish reference centre perspective could be considered a cost-effective strategy [ 9 ]. The benefits from NGS relative to the single gene testing include the number of alterations detected, treatment with targeted therapies and clinical trial enrollment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the Focus Group and the reviewed literature emphasize this aspect, including a previous study showing that the determination of some of the biomarkers is funded by different pharmaceutical companies in more than 50% of the hospitals [ 5 ]. Moreover, it has recently been estimated that the analysis of molecular diagnosis by NGS versus sequential single testing in metastatic non-small cell lung cancer patients from a Spanish reference centre perspective could be considered a cost-effective strategy [ 9 ]. The benefits from NGS relative to the single gene testing include the number of alterations detected, treatment with targeted therapies and clinical trial enrollment.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of how they are allocated, it must be considered that their value lies in the combination of both, so it is a joint product [ 10 ]. And as argued above, the strategy of using NGS can be cost-effective in Spain [ 9 ], but also in other countries like the US [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings reinforce the immediate clinical value of comprehensive panel sequencing for actionable mutation detection and its applicability for most patient samples, even those with low tumor content. The adoption of comprehensive panels has been shown to have diagnostic and economic value when compared with serial single-gene testing in advanced NSCLC [2,[45][46][47]. Overall, it is previously reported that multigene panels increase the proportion of patients with access to targeted therapy when compared with combinations of single-gene tests [46], resulting in an increase in life years or quality-adjusted life years [2,47] while being cost-neutral or cost-saving to the health system [2,[45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Although cost-effectiveness studies favored NGS testing before deciding on first-line treatment for advanced NSCLC 95,96 , costs with novel testing methodologies, turnaround time, and access restriction to some targeted therapies can still make it difficult to completely abandon older testing methods. Also, genomic testing protocols may vary geographically.…”
Section: Advances In Molecular Testing Methodologiesmentioning
confidence: 99%